Palynological studies of post-glacial deposits with different water relations and muskeg environments. - Chen, Margaret Wei-yi (My University, 1968)
This investigation is intended to explore and trace the trend in the development of muskeg (organic terrain), of which water is an essential factor. The work proceeded as follows: field work and laboratory pollen macerations, identification of pollen and spores and pollen counting; and finally the analysis of the results obtained.
The results do not favour the establishment of a strong relationship between water in muskeg and vegetation in situ. However, this needs further test. On the other hand, there are relationships found between pollen species, and also interesting natural grouping was observed to exist in the bogs studied, due to unknown factors.
Keywords: biology, palynological, holocene, deposit, Parry Sound